The reality of intellectual security among students of the College of Basic Education, Tal Afar University A descriptive study - Ali Suleiman; Hamid Khalaf; Aymen Jassim (University of Mosul-college of Basic Education, 2024)
The current research aims to identify the reality of intellectual security among students at Tal Afar University. The descriptive approach was used as it is the most capable of describing a specific phenomenon. The sample consisted of (100) male and female students from the second stage of the mathematics department, morning study for the academic year (2023 - 2024). They were chosen randomly. To achieve the goal of the research, the researchers prepared an intellectual security scale, which consisted of (30) items with three alternatives (always - sometimes - rarely). The validity and reliability of the tool, as well as its psychometric properties, were verified. After analyzing the research data statistically using a one-sample test, the results showed: There is no statistically significant difference at the significance level (0.05) in the average scores of the intellectual security scale among students of the College of Basic Education, Tal Afar University. The researchers reached a set of conclusions and recommendations, as well as their proposals for future research in this aspect